Hubungan Intensitas Penggunaan Teknologi Informasi Dan Komunikasi Dengan Keterlibatan Belajar Mahasiswa Generasi Z - Tejarukmi Mutiara; Dianti Endang Kusumawardhani (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
This study aims to examine the relationship between the intensity of the use of information and communication technology in education to the learning engagement of Generation Z students. The method used is filling out a questionnaire regarding learning involvement by Generation Z students (n = 108). The result shows that the time period for the first time to recognize and the duration of the use of information and communication technology is negatively correlated with student learning engagement. Meanwhile, the use of information and communication technology aimed at academic interests is positively correlated to student learning engagement. Generation Z students should be able to regulate themselves to be able to utilize information and communication technology for academic purposes.